Proactive personality, voice behavior, and the roles of team social exchange - Nikodemus Hans Setiadi Wijaya (Jurnal Siasat Bisnis, 2021)
Purpose: This research examined the links of proactive personality, team social exchange comprising leader-member exchange (LMX) and team-member exchange (TMX), and two types of voice behavior comprising team-voice behavior (TVB) and organizational-voice behavior (OVB). Under self-determination theory, the current study proposes the mediating effects of team social exchange on proactive personality and voice behavior.Design/methodology/approach: This study was based on online questionnaire surveys from 238 Indonesian employees. A structural equation modeling (SEM) analysis with the bootstrapping technique was used to examine the hypothesized relationships.Findings: The current study found 1) the significant influences of proactive personality on both LMX and TMX; 2) the significant influences of proactive personality on TVB and OVB; 3) the influences of LMX and TMX on both TVB and OVB; and 4) the partial mediating effects of LMX and TMX.Research limitation/implications: A single-rater method in data collection may occur in some extents of common method variance (CMV). The findings contribute to the empirical evidence of the pivotal role of team social exchange on the relationships between proactive personality and two types of voice behavior.Practical implications: Since voice behavior may have positive impacts on the organization’s performance and survival, organizations may wish to include proactive attributes in the HRM process (e.g., selection, promotion) and may also want to place more attention on efforts directed at improving team social exchange relationships. Also, organizational practitioners are advised to promote team social exchange as an additional factor impacting voice behavior. In addition, the proposal of two types of voice behavior may offer a wider scope of this construct. Originality/value: This study proposes two types of voice behavior, namely team-voice behavior (TVB) and organizational-voice behavior (OVB) which extend the scope of this construct.